The Use of Indonesian Terms in Sports - Analis Adinda Nurwulan; Pesty Nur Annisa; Zeina Rahmana Putri; Rama Zidane Alfitra; Muhammad Fawwaz Nur Rizqy; Mochamad Whilky Rizkyanfi (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objectives. The objective of this study is to analyze the frequency of Indonesian sports-related vocabulary in contemporary sporting contexts. Sports terminology encompasses all the lexicons and phrases that delineate various aspects of athletic activities, such as techniques, regulations, and circumstances. These terminologies can either be borrowed from foreign languages like English or be indigenous to Indonesia. Some sports terminologies are generic and can be applied to multiple sports, while others are specific to particular events. In Indonesia, numerous sports-related terminologies are utilized, including athlete, division, goal, and pass. The study aims to determine the prevalence of these types of terminologies in the current sports world of Indonesia. Materials and methods. In literary inquiry, researchers rely on written sources such as books, journals, and articles as their primary data. This approach is commonly used in qualitative research and eliminates the need for researchers to conduct direct observations or interviews to gather information. Essentially, instead of engaging with subjects directly or observing their actions, researchers analyze existing written material related to the topic at hand. Results.